Cognitive performance in patients with implantable cardioverter defibrillators: Associations with objective sleep duration, age and anxiety. (13th December 2018) - Curtis, Ashley F.; Roth, Alicia J.; Sears, Samuel F.; Conti, Jamie B.; Berry, Richard B.; Dzierzewski, Joseph M.; Rathinakumar, Himangshu; McCrae, Christina S.
Abstract: Sleep disturbance and anxiety are highly prevalent in patients with implantable cardiac defibrillators (ICDs). There is limited research, however, on the associations between cognitive performance and sleep parameters, age and anxiety. Forty‐one patients with ICDs and self‐reported sleep disturbance completed 14 days of actigraphy ( M age = 60.3, SD = 12.3) measuring total sleep time (TST), and a computerized cognitive test battery measuring processing speed and attention (i.e. simple reaction time and symbol digit modality task [SDMT]) and executive function (i.e. flanker task, letter series task and N‐back task). Multiple regressions determined whether independent effects of TST, age and anxiety, as well as interactive effects of TST and age, predicted cognitive performance. TST predicted performance on two tasks of executive function (i.e. letter series and N‐back task), as well as an attentional vigilance and processing speed task (i.e. SDMT), and this did not depend on patient age. On letter series, N‐back and SDMT, longer TST predicted better performance. Increasing age was a predictor of worse performance on SDMT and flanker tasks. No other predictors were associated with task performance. Results show that sleep duration, not anxiety, may be an important predictor of higher‐order cognitive functioning and lower‐order tasks measuring processing speed and attention in ICD patients, with longer sleep duration showing greater benefit for performance.